Cyclic changes in T2* relaxometry of human uterus during the menstrual cycle using BOLD MR imaging. Issue 156 (November 2022) - Li, Yajie; Lai, Mao; Li, Qing; Fu, Caixia; Zhang, Qi
Highlights: This study firstly explored T2* values of uterine zone structures in menstrual cycle. T2* values can be helpful for evaluating dysmenorrhea and oxygenation of endometrium. T2* values can be useful in monitoring hypoxia in gynecological diseases. Abstract: Purpose: To evaluate dynamic changes of T2* values within the endometrium, junctional zone and myometrium during the menstrual cycle using blood oxygen level-dependent (BOLD) magnetic resonance imaging. Method: Volunteers underwent MRI scans on menstrual phase, ovulatory phase and luteal phase, including T2-weighted imaging and BOLD MR imaging. Multi-gradient-recalled echo (MGRE) sequence was used to obtain BOLD MR images. T2* values of different uterine layers, including endometrium, junctional zone and myometrium, on sagittal images were analyzed quantitatively. Results: Twenty-four subjects calculated T2* values successfully. The T2* values of each zonal structure during menstruation were significantly lower than those during ovulatory phase ( P  < 0.05) and luteal phase ( P  < 0.001). The T2* value of junctional zone was significantly lower than that of the myometrium over all three menstrual phases ( P  = 0.000, menstrual; P  = 0.000, ovulatory; P  = 0.001, luteal). The mean T2* value in endometrium during the ovulatory phase was the highest of the uterine zones over menstrual cycle. During menstrual phase, there was no statistical difference between endometrium and junctional zone ( P  > 0.05). Conversely, the comparison of the T2* values between endometrium and myometrium, junctional zone and myometrium both showed significant difference ( P  = 0.000). The mean T2* values within endometrium during ovulatory phase and luteal phase were significantly higher than those within junctional zone and myometrium ( P  < 0.05). Conclusions: Cyclic changes of T2* values in each zonal structure of the uterus were revealed during the menstrual cycle by means of BOLD technique, which may be potentially beneficial in investigating dysmenorrhea, guiding assisted reproductive technologies and monitoring hypoxia in gynecological tumors.